2004
DOI: 10.1016/s0167-8140(04)80035-5
|View full text |Cite
|
Sign up to set email alerts
|

Late effects from hadron therapy

Abstract: Successful cancer patient survival and local tumor control from hadron radiotherapy warrant a discussion of potential secondary late effects from the radiation. The study of late-appearing clinical effects from particle beams of protons, carbon, or heavier ions is a relatively new field with few data. However, new clinical information is available from pioneer hadron radiotherapy programs in the USA, Japan, Germany and Switzerland. This paper will review available data on late tissue effects from particle radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 103 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…41 The hypothesis of reduced late side effects with proton therapy has been investigated intensely and tends to be correctly supported, although large uncertainties in the relative biological effect, among others, remain. [42][43][44][45][46] In addition, improvements in the treatment delivery equipment further reduce the amount of secondary neutron production, which is the main contributor to the scattered dose to the normal tissue. [47][48][49] Although the occurrence of secondary tumors for lung cancer patients could be considered irrelevant due to the short life expectancy, the expected reduced carcinogenic risk should be mentioned with respect to the changing NSCLC population and overall treatment improvements.…”
Section: Discussionmentioning
confidence: 99%
“…41 The hypothesis of reduced late side effects with proton therapy has been investigated intensely and tends to be correctly supported, although large uncertainties in the relative biological effect, among others, remain. [42][43][44][45][46] In addition, improvements in the treatment delivery equipment further reduce the amount of secondary neutron production, which is the main contributor to the scattered dose to the normal tissue. [47][48][49] Although the occurrence of secondary tumors for lung cancer patients could be considered irrelevant due to the short life expectancy, the expected reduced carcinogenic risk should be mentioned with respect to the changing NSCLC population and overall treatment improvements.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the majority of studies with cancer patients receiving proton therapy instead of conventional photon therapy have concluded that late effects, including cataracts, induced by protons are nearly equivalent to what one would expect from equivalent photon doses. RBE values are around 1.0, except near the very end of the stopping Bragg peak (Blakely and Chang, 2004).…”
Section: Eyementioning
confidence: 96%
“…These reports suggest that the variation of cellular nature may result in RBE changes for cell-killing that should be exploited before clinical application. From radiobiological studies, carbon beam treatment may show a high RBE for cell-killing in cells that are repair proficient and radioresistant to X- or γ-rays [32] but also may imply a greater risk in normal tissue for late effects than X- and γ-rays or protons [33]. Preclinical studies for interested normal or tumor cell lines are therefore fundamental for assessing these radiobiological properties of different cell and tissues.…”
Section: Factors Influencing Carbon Beam Rbementioning
confidence: 99%